An Efficient Transient Expression System for Enhancing the Generation of Monoclonal Antibodies in 293 Suspension Cells - Zhang, Guoquan; Liu, Jie; Fan, Wanting; Chen, Qianyi; Shi, Bin (Current Pharmaceutical Biotechnology, 2017)
Background: Recombinant monoclonal antibodies (mAbs) are useful in research, diagnosis, and therapy. The increased demands of recombinant mAbs require efficient production systems. A variety of expression vectors have been developed for stable or transient production of mAbs in mammalian cells. Although a few commercial expression systems of mAbs can be listed, the high expense often impedes academic research. Methods: In this study, we described the development of a transient mammalian system based on a bicistronic vector, which contained an internal ribosome entry site (IRES) and enhancer elements to express the IgG1 light chain (LC) and heavy chain (HC) in one transcript. Optimization of all components of the expression system, including gene transfer methods and regulatory elements, yielded maximal expression levels in serum-free 293 suspension cells (Freestyle 293-F). Results: This method enabled consistent production of the anti-programmed cell death protein 1 (PD-1) mAb up to 300 mg/L in less than one week under transiently transfected conditions. Furthermore, purified anti-PD-1 IgGs showed specific affinity to the target antigen human PD-1 and PHA-stimulated human T cells. Conclusion: The simplicity of the procedure made it suitable for the fast and high-yield production of IgG antibodies in small scales, which expedited the screening of a large number of recombinant candidates.
Keywords: PD-1